The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1016/j.jpeds.2016.07.025
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Function in Youth: A Biomarker Modulated by Adiposity-Related Insulin Resistance

Abstract: Childhood obesity, particularly abdominal adiposity, is associated with endothelial dysfunction manifested by worse reactive hyperemia and higher AIx. Insulin resistance appears to mediate this relationship.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 36 publications
2
26
2
1
Order By: Relevance
“…In adults, the presence of insulin resistance in obesity may mediate this relationship . The relationship of endothelial function to insulin sensitivity in adolescents is less clear as a relationship has been found in some, but not all studies, and may be dependent on how endothelial function and insulin sensitivity are assessed . In the current study we did not find a relationship between endothelial function and insulin sensitivity.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…In adults, the presence of insulin resistance in obesity may mediate this relationship . The relationship of endothelial function to insulin sensitivity in adolescents is less clear as a relationship has been found in some, but not all studies, and may be dependent on how endothelial function and insulin sensitivity are assessed . In the current study we did not find a relationship between endothelial function and insulin sensitivity.…”
Section: Discussioncontrasting
confidence: 75%
“…This may indicate that we used the wrong markers. Tomosa et al, however, found no relationship between reactive hyperemia and tissue necrosing factor‐α, but did find a relationship for AIx 75 . It is, also, possible that these relationships may not develop until a later age.…”
Section: Discussionmentioning
confidence: 94%
“…The reduction of insulin-induced vasodilatation in overfed rats may be related to a general impairment of arterial vasodilatation during the first stages of weight gain, as both the relaxation in response to acetylcholine, which is mediated by nitric oxide release from the endothelium, and to sodium nitroprusside, which acts directly on the vascular smooth muscle, were reduced in early overfed rats. Likewise, it is reported that vasodilatation to reactive hyperemia correlates negatively with body fat in adolescents [37]. As previously reported [38,39], the vascular insulin resistance may be due to both increased vascular inflammation and oxidative stress, since both the mRNA levels of pro-inflammatory and pro-oxidant markers were upregulated in overfed rats.…”
Section: Discussionsupporting
confidence: 61%
“…In OHAs with dysglycemia (prediabetes and T2DM), the presence of NAFLD is associated with worse endothelial function, a biomarker of subclinical atherosclerosis, as indicated by lower reactive hyperemia index (nitric oxide dependent vascular function), higher augmentation index (a measure of peripheral vascular stiffness) [ 27 , 29 ], and higher levels of circulating inflammatory markers. These measures of vascular function were related to the hepatic fat content, independent of total body and visceral adiposity, and other CVD risk markers of glycemia, and blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…The augmentation index (AIx) is a measure of arterial stiffness. It is usually a negative number calculated as the difference between the early (P1) and late (P2) systolic peaks of the pulse wave relative to the early peak wave (P2 – P1 / P1) expressed as a percentage [ 28 ], and adjusted to a standard heart rate of 75 beats per minute (AIx-75) [ 29 ]. A higher AIx (less negative number) reflects greater arterial stiffness.…”
Section: Methodsmentioning
confidence: 99%